Acrolocated gloves and socks syndrome due to PARVOVIRUS B19. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. A 7-year-old child was observed for the presence of punctate lesions prevailing on the hands, feet, chin and penis (Fig. 1, 2, 3). The lesions started 4 days before accompanied by fever and vomiting; there were no other general signs and arthralgias. The physical examination showed puntate petechiae affecting the feet and hands, both the palmar and the plantar surface, the penis, the axillary and perioral regions; there were not mucosal lesions and adenopathy. The general symptoms and purpuric lesions subsided in a week. Blood tests, including a complete blood count were within normal limits, as well as the inflammatory markers, transaminases and coagulation tests. After healing IgM antibodies against parvovirus B19 were 65.5 U.A. (positive> 11.5), while the IgG antibodies against the same virus were 14.9 AU (positive> 11.5), leading to the final diagnosis of acrolocated gloves and socks syndrome due to Parvovirus B19.